THE ROLE OF CUSTOMER RELATIONSHIP MARKETING ON BRAND TRUST: RELATIONSHIP MARKETING THEORY APPROACH IN THE DIGITAL BANKING INDUSTRY - Feni Khairifa; Safrin Safrin (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The digital banking industry in Indonesia is growing rapidly along with the increasing adoption of mobile banking applications. This growth was followed by a high level of customer awareness of transaction security and the reliability of digital services, making building brand trust a strategic challenge for banks. This study aims to analyze the role of Customer Relationship Marketing (CRM) on Brand trust in the digital banking industry in Medan City based on the Relationship Marketing theory approach, as well as measure the contribution of bank brand reliability according to the five dimensions of CRM: trust, commitment, communication, conflict handling, and bonding/empathy. A causal associative quantitative approach was used by involving 200 customers who were active users of digital banking services selected by purposive sampling. Structural Equation Modeling based on Partial Least Square (SEM-PLS) was applied for data analysis. The five dimensions of CRM show positive and significant influence results on Brand trust (R² = 0.612). Trust makes the largest contribution, followed by commitment, bonding/empathy, communication, and conflict handling. These findings reinforce the relevance of Relationship Marketing theory in the context of digital banking and have implications for managerials, that banks need to prioritize transactional trust strengthening strategies and long-term commitments to build sustainable brand trust among digital customers